101 reasons: to switch to the Mac - McElroy, Mark (Que, 2006)
You've seen lots of "how to" information ... but 101 Reasons to Switch to a Mac offers the "why to"! Inside, instead of tech-talk and speed tests, 101 Reasons to Switch to the Mac offers true stories and unbiased advice from a long-time Windows user who, along with a million others in 2005, made the switch to a Mac. The chapters explore the benefits of working with a Mac, the power of the Mac OS X operating system, and the advantages of owning a computer that "just works." The comprehensive software guide recommends great applications that make short work of everyday tasks like surfing the web, ripping music, watching movies, retouching photos, laying out brochures, and much more. You'll also find pointers to great websites packed with resources for switchers and new Mac owners alike. Already a Mac user? This Short Cut makes the perfect gift for friends and family who haven't yet discovered the joy of switching. The next time a PC user says, "Give me one good reason to switch!" you'll be prepared ... with 101 Reasons to Switch to a Mac . Here are just a few of the 101 reasons! Why Mac OS X is the World's Coolest OS Yes, you can have it all-Macs Do Windows Powerful Bundled Software has everything you'll need or want Find out why wireless networking is easier with a Mac The Macs fast performance makes it all worthwhile How the Mac protects you from viruses and hackers 1. It Just Works 2. Ooohs and Aaahs 3. Macs Are Better for Beginners 4. Easy Setup 5. Faster Boots 6. Ready and Waiting 7. Greater Stability 8. Easy Software Installation 9. The Apple Store 10. They're Compatible 11. Macs Do Windows 12. .Mac ("Dot Mac") 13. Easier Wireless Networking 14. Protection from Viruses 15. Protection from Hackers 16. Productivity 17. Intelligent Monitor Management 18. Smoother Media Playback 19. Accessible Software Authors 20. Digital Photography Made Simple 21. Do More with Your Media 22. It Works Like an iPod 23. Native PDFs 24. Powerful Bundled Software 25. Blazing Fast Performance 26. The Value Question 27. Switching Is Easy 28. The MacBook 29. The MacBook Pro 30. iMac 31. Mac mini 32. iPods 33. Mighty Mouse 34. Built-in WiFi and Bluetooth 35. Airport Extreme Wireless Networking 36. Vista 2.0 Today? 37. Unix Under the Hood 38. The Mac OS X GUI 39. The Dock 40. Exposé 41. Spotlight 42. Dashboard 43. Spaces 44. Time Machine 45. Alex 46. Automator 47. Smart Folders 48. Auctions 49. Backup 50. Blogging 51. Charting 52. Chatting 53. Creative Writing 54. Customi ...